Theory of flight - Von Mises, Richard, 1883-1953 (Dover books on physics, engineering., 1959)
Perhaps the most balanced, well-written account of fundamental fluid dynamics ever published. Mises' classic avoids the formidable mathematical structure of fluid dynamics, while conveying? by often unorthodox methods? a full understanding of the physical phenomena and mathematical concepts of aeronautical engineering. An outstanding textbook.? Scientific, Medical and Technical Books.